The effective ingredients of social care support at home for people with dementia: a literature review - Argyle, Elaine; Kelly, Tony; Gladman, John R.F.; Jones, Rob (Emerald, 2017)
Purpose: Formal ties between the theatre and research dissemination have only recently developed and its general efficacy is largely unknown. Here the purpose of this paper is to redress this neglect by examining the effectiveness of a research-based theatrical event in promoting dementia knowledge transfer with a group of front line care workers. The event ran over eight days and consisted of an original theatrical production followed by a chaired audience discussion and workshops.